(untitled) (Gestão & Regionalidade, 2018)
Approaches that deal with cooperation among companies in a supply chain generally consider the beneficial aspects of this cooperation, such as gains in competitiveness and productivity, but do not consider the fact that the cooperative relations occur asymmetrically in the chain, due to the heterogeneity of the participants. In order to analyze the cooperation, learning and innovation processes in a chain whose relationship is known as asymmetrical and that the degree of competitiveness has increased in recent years, as in the case of the Brazilian textile industry, this work was based on interviews with 14 textile companies from Americana region, São Paulo, Brazil. These interviews showed the existence of superficial relations of cooperation among the members of the chain interviewed, and that this form of cooperation implies in the inexistence of a systematic and coordinated process of knowledge acquisition by companies and, consequently, of technological and organizational innovations. Keywords: Innovation; learning; cooperation; textile industry.